PRARANCANGAN PABRIK ISOBUTIL AKRILAT DARI ASAM AKRILAT DAN ISOBUTANOL KAPASITAS 40.000 TON/ TAHUN - , OKI HARYO NUGROHO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia is a developing country who is currently developing whole aspects including its industries. The growth, especially in industrial sector, will help the countryâs economical aspect such as an increasing state revenue and lesser number of unemployment. One example of industry is the industry of isobutyl acrylate. Isobutyl acrylate can be applied in numerous chemical industry, mostly as raw material for paint industry, floor polishing, adhesives etc. Those mentioned industries can be found anywhere around the globe, so we are clear that Isobutyl acrylate industry has a good prospect for the future. This isobutyl acrylate factory will be designed to maintain the production capacity of 40.000 tons per year. This petrochemical factory adapting the esterification process of acrylic acid with isobutanol. It has been calculated that for the production scale as mentioned before, this factory needed 24.896,6 tons of acrylic acid per year and isobutanol around 24.428,5 tons per year as the raw material. Sulfuric acid were also added to the process as catalyst, in which the demand of this chemical substance will be around 1.262,7 tons per year. This factory are also designed to use 519.365,1 tons of water per year as utility water, while 550 Kva of electricity will be consumed. 974,8 ft 3 of diesel fuel will be provided for the power generator in case of power failure. The total of pressurized air consumed for this factrory will be around 100 m 3 per hour. This factory will be built in 2020 in Cilegon industrial area, west Java. The area needed will be 3 Ha including housing complex and area to expand. This factory will operate 24 hours per day and 330 days per year. The number of worker will be around 221 people. Based on the economic evaluation during the predesign calculation, The fix capital required to build this factory, FCI, will be around US$9.914.670,07 + Rp.51.951.255.917,16 while the working capitals are US$21.688.696,88 + Rp5.543.210.864,15. Profit before tax will be Rp. 54.212.963.113,50/year and the profit after tax will be Rp. 27.106.481.556,50/year. The return of investment (ROI) before tax will be 35,88% while after tax it will be 17,94%. The pay out time before tax will be 2,25 year while after tax it will be 3,78 years. The break event point of this factory reached at 52,15% of production while the shut down point is 36,68%. Based on those parameters mentioned above and the further literatures study, it was concluded that the investment for this factory is interesting for further review.